"Som mamma betalar påverkar det mina kläder" : En uppsats om svenska ungdomars identitetsbildning genom mode och hur de påverkas i relation till sina kläder - Nejdenlo,Alexandra (2023)
This paper takes a closer look at a Swedish group of teenagers' usage of fashion in their identity development in an effort to contribute to the understanding of fashion usage in youth culture. By involving them in discussions and interviews, and basing it in theory this paper comes to a somewhat understanding in how phenomena such as religion, gender identity, and celebrity influence the way Swedish youth use clothes and influence their sense of self. The paper concludes that while the group does not strongly identify in using fashion for identity development purposes, developing a sense of style proves important in recognising the process of identity exploration.
Keywords: Mode; Ungdomar; Ungdomsmode; Tonårsmode; Kläder; Identitet; Identitetsbildning; Tonåringar